Genetic Diversity and Population Structure of Similar Named Aromatic Rice (Oryza sativa L.) Landraces of Bangladesh (SAARC Journal of Agriculture, 2022)
Assessment of thirty-six similar named aromatic rice landraces of Bangladesh was analyzed using 36 microsatellite markers to characterize the landraces and also to establish the sovereignty of the Bangladeshi rice gene pool. With an average of 3.03 per locus, overall 109 alleles differed from 2 to 5 were detected at 36 microsatellite loci across the 36 aromatic rice landraces. With an average of 0.48, the diversity of genes ranged from 0.15 to 0.74. The polymorphic information content (PIC) values ranged from 0.14 (RM500, RM554) to 0.69 (RM496), with an average of 0.41, revealed many variations among the studied landraces. The recurrence of the most prevalent allele at each locus ranged from 31.00% (RM496) to 96.00% (RM500 and RM554). At any given locus, on average 64.33% landraces out of 36 contributed a familiar major allele. For identification and diversity estimation of aromatic rice landraces, RM496 was the finest marker as affirmed by PIC values. Two clusters were revealed with a similarity coefficient of 0.45 by a UPGMA dendrogram in SSR. All the landraces were also divided into two groups (A and B) through the model-based clustering method, confirmed by UPGMA cluster analysis. Some of the SSR markers (RM1, RM489, RM39, RM474, RM2, RM214, RM21, and RM206) generated unique alleles that were specific to particular landraces and were useful for varietal identification. Besides, the evaluation of genotypic data demonstrated the landraces under this study provided noticeable genetic diversity. Meanwhile, for the future breeding program, the similarly named landraces need to be safeguarded.SAARC J. Agric., 19(2): 57-71 (2021)